Kontribusi Keterampilan Guru Abad 21 Terhadap Implementasi Kurikulum 2013 di SMK 1 Sumbar - Nurpendah, Ririn; Rizal, Fahmi; Sukardi, Sukardi (Jurnal Aplikasi IPTEK Indonesia, 2020)
The problem in this study is that teachers still have difficulty in carrying out student attitude assessment through the attitude assessment rubric, in the 2013 curriculum students are required to be more active and the teacher acts as a facilitator, but the teachers in SMK 1 West Sumatra have not been able to position themselves as facilitators. So the learning objectives that have been outlined by the 2013 curriculum have not been maximally achieved. Furthermore, the lack of use of instructional media as a learning support tool, so that learning implemented by SMK 1 West Sumatra is less varied, learning direct learning models that are still not maximally implemented by teachers and the lack of awareness of SMK 1 West Sumatra teachers in participating in curriculum training in 2013. The research objective is to explain the relationship of 21st century teacher skills with the implementation of the 2013 curriculum at SMK 1 West Sumatra. This research uses correlational quantitative research. Based on the research results obtained that there is a positive and significant relationship of 21st century teacher skills with the implementation of the 2013 curriculum at SMK 1 West Sumatra with a contribution percentage of 50.4%.